A Prospectus for Constraining Rapid Cloud Adjustments in General Circulation Models. (30th August 2018) - Nam, Christine; Kühne, Philipp; Salzmann, Marc; Quaas, Johannes
Abstract: Rapid cloud adjustments are an important component of the atmosphere's total response to increased CO2 concentrations. Unfortunately, scientific understanding of rapid shortwave cloud adjustments is rather poor. State‐of‐the‐art 5th Coupled Model Intercomparison Project models showed large uncertainty in regard to rapid cloud adjustments. This study determines whether large‐eddy simulations may, in principle, be used as a reference, thanks to their ability to resolve cloud dynamics and thermodynamics, to constrain rapid shortwave cloud adjustments in general circulation models. This is an open question since large‐eddy models can only be run over limited domains, for a short period of time, and are influenced by boundary conditions. Using the Icosahedral Non‐hydrostatic global climate model—Atmospheric component (ICON‐A), we examine shortwave rapid cloud adjustments over central Europe, which is found to be representative of shortwave rapid cloud adjustments over Northern Hemispheric global continents in the 5th Coupled Model Intercomparison Project models. This work finds (i) a couple of days of simulation is sufficient to get a clear signal in the net top‐of‐atmosphere radiative balance to emerge after a 4xCO2 perturbation and (ii) use of present‐day meteorological and CO2 concentrations for boundary conditions in global simulations is not an issue for short lead times, up to ∼36 hr. We also found that atmospheric processes influencing shortwave rapid cloud adjustments over central Europe are largely thermodynamically driven changes in local cloud dynamics and are rather independent of the synoptic‐scale and circulation effects on short timescales (<2 days). These results imply that high‐resolved large‐eddy simulations over a limited area can be instructive for assessing and constraining global rapid cloud adjustments. Plain Language Summary: Our work demonstrates that large‐eddy simulations may, in principle, be used to constrain rapid adjustments in general circulation models despite the fact that large‐eddy models can only be run on over limited area, run for a short period of time, and are influenced by boundary conditions. Key Points: Rapid shortwave cloud adjustments over central Europe in ICON‐A GCM are representative of CMIP5 models over Northern Hemispheric continents Using present‐day meteorological and CO2 concentrations for later boundary conditions in 4xCO2 simulations is not an issue up to 36 hr Shortwave rapid cloud adjustments up to 36 hr may be evaluated in large‐eddy simulations